Studying the Radial and Tangential Velocity Components of the Epithelization Healing Post Photorefractive Keratectomy Surgery of the Human Eye - Ghaeb, Nebras H. (Al-Khwarizmi Engineering Journal, 2020)
Photorefractive keratectomy (PRK) is the refractive technique that began with a physical scraping of the epithelial layer of cornea subsequent by laser treatment. Post this procedure to about 48 hours the removed epithelial layer regenerated to protect the eye again. The regeneration process (called re-epithelization) started from the limbus of the cornea toward the central part of it. The re-epithelization mechanism consists of a change in cell density (mitosis) and cell concentration (migration) with a velocity in two directions: radial and tangential. In the present study, an estimation for both radial (responsible for the overlapped layers toward the outward direction of the cornea) and tangential components (contour shape wave from limbus to the center) has been done for the first time, not like the previous studies that always estimate the velocity values of the re-epithelization only. Results showed that the trend shape of both components agrees with the kinematic behaviour of the mitosis and migration, where the maximum cell density fluctuated toward the central part in exponential decay shape. For a healing diameter of 2mm, the maximum redial velocity was 16.85 µm/h, while the maximum tangential velocity was 55.48 µm/h. These two components give a speed of re-epithelization of 58 µm/h which agrees with the biological and practical healing speed measured of 60 µm/h. Estimating these two components will open the way to understand the relationship between the total epithelial layer required and the total healing time to control the medication period for the patient post-surgery.